Myo-inositol supplementation improves cardiometabolic factors, anthropometric measures, and liver function in obese patients with non-alcoholic fatty liver disease - Arefhosseini, Sara; Roshanravan, Neda; Tutunchi, Helda; Rostami, Somayyeh; Khoshbaten, Manuchehr; Ebrahimi-Mameghani, Mehrangiz (Frontiers in Nutrition, 2023)
Purpose To investigate the effects of Myo-inositol (MI) supplementation on glucose homeostasis, lipid profile, liver function, anthropometric measures and blood pressure in patients with non-alcoholic fatty liver disease (NAFLD). Methods This double-blinded placebo-controlled randomized clinical trial was carried out on 48 obese patients with NAFLD who were randomly assigned into either MI (4g/day) or placebo (maltodextrin 4g/day) along with dietary recommendations for eight weeks. Glycemic indices, lipid profile, liver function, anthropometric measures, and blood pressure were evaluated pre-and post-intervention. Dietary intakes were assessed using a 3-day 24 hours recall. Results Anthropometric measures decreased significantly in both groups while the reduction in weight (p= 0.049) and systolic blood pressure (p=0.006) in MI group was significantly greater than the placebo group after adjusting for baseline values and energy intake. Although energy and macronutrient intakes decreased significantly in both groups, between group differences were not significant after adjusting for the potential confounders. MI supplementation led to a significant reduction in serum fasting insulin (p=0.008) and HOMA-IR (p=0.046). There were significant improvements in lipid profile, liver enzymes, aspartate aminotransferase/alanine aminotransferase ratio as well as seum ferritin level in the MI group, compared to the placebo group at the endpoint. However, no significant between-group differences were found in liver fibrosis score as well as aspartate aminotransferase to platelet ratio index (APRI). The estimated number needed to treat (NNT) for one grade reduction in liver steatosis was 3. Conclusion MI supplementation could significantly improve not only insulin resistance and lipid profile but also serum liver enzymes.